Market participation and pastoral welfare in drought-prone areas: A dose-response analysis - Yitayew, Asresu; Kassie, Girma; Yigezu, Yigezu (Elsevier, 2023)
The low market participation of pastoral livestock producers is a challenge to the development of a climate-resilient economy in drought-prone areas. Without deliberate and well-designed efforts to transform livestock production into a thriving profit-oriented commercial business, the development of pastoral societies will remain far-fetched. By applying bivariate selection model and dose-response function to a case study of 357 pastoral households in Ethiopia, this study examines pastoralists’ participation in goat markets and the impact of participation on per capita income, poverty headcount, and poverty gap. Our results show that the propensity and intensity of participation of pastoralists in goat marketing were influenced by flock size, transaction costs (TC), and access to veterinary services. An important finding in this study is that pastoralists are willing to pay for marketing services up to 97 % of the total variable TC, indicating the financial feasibility of public investment in the development of market infrastructure through cost recovery schemes. The results also reveal that participation in goat marketing has a positive impact on per capita income, poverty headcount, and poverty gap. These findings shed some light on more practical strategies for poverty reduction among pastoralists